Enabling Electron Injection for Microbial Electrosynthesis with n‐Type Conjugated Polyelectrolytes. Issue 37 (3rd August 2022) - Quek, Glenn; Vázquez, Ricardo Javier; McCuskey, Samantha R.; Kundukad, Binu; Bazan, Guillermo C.
Abstract: Microbial electrosynthesis—using renewable electricity to stimulate microbial metabolism—holds the promise of sustainable chemical production. A key limitation hindering performance is slow electron‐transfer rates at biotic–abiotic interfaces. Here a new n‐type conjugated polyelectrolyte is rationally designed and synthesized and its use is demonstrated as a soft conductive material to encapsulate electroactive bacteria Shewanella oneidensis MR‐1. The self‐assembled 3D living biocomposite amplifies current uptake from the electrode ≈674‐fold over controls with the same initial number of cells, thereby enabling continuous synthesis of succinate from fumarate. Such functionality is a result of the increased number of bacterial cells having intimate electronic communication with the electrode and a higher current uptake per cell. This is underpinned by the molecular design of the polymer to have an n‐dopable conjugated backbone for facile reduction by the electrode and zwitterionic side chains for compatibility with aqueous media. Moreover, direct arylation polycondensation is employed instead of the traditional Stille polymerization to avoid non‐biocompatible tin by‐products. By demonstrating synergy between living cells with n‐type organic semiconductor materials, these results provide new strategies for improving the performance of bioelectrosynthesis technologies. Abstract : Integrating Shewanella oneidensis  MR‐1 with a newly synthesized n‐type conjugated polyelectrolyte forms a 3D conductive network that allows efficient electron transfer from electrode to living cells, thereby enabling microbial electrosynthesis. The one‐step self‐assembly process offers a simple and effective strategy to improve bioelectrochemical systems.